Antibiotic resistance and prevalence of class 1 and 2 integrons in Escherichia coli isolated from hospital wastewater - Ranjbar, Reza; Zeynali, Maryam; Sohrabi, Nooshin; Kamboh, Asghar Ali; Moshaveri, Arman (Faculty of Medicine, Trisakti University, 2018)
BACKGROUND Hospital wastewaters may contain antibiotic resistant bacteria such as Escherichia coli. These E. coli harbor integron genes that are responsible for antibiotic resistance. The purpose of the current study was to evaluate the frequency of class 1 and 2 integrons in environmental antibiotic resistant E. coli strains isolated from the hospital wastewaters in Tehran, Iran.METHODSAs a descriptive cross-sectional study, this research was performed from April to September 2015 on hospital wastewaters in Tehran. Bacterial isolation and identification was performed by standard biochemical and bacteriological procedures. Susceptibility testing was done by employing the disk diffusion method using different antibiotics. Total DNAs were extracted to evaluate the presence of class 1 and 2 integrons by using the polymerase chain reaction (PCR) method with specific primers. RESULTSFifty E. coli strains were isolated and identified from the wastewaters of 25 hospitals in Tehran. The phenotype results showed that 46 isolates (92%) were resistant to at least one antibiotic and 27 isolates (54%) were multidrug resistant. PCR showed that 35 (70%) and 20 (40%) of the isolates had class 1 and 2 integrons respectively and 14 isolates (28%) had both class 1 and class 2 integrons.CONCLUSIONThis study has shown a considerable presence of class 1 and class 2 integrons in E. coli strains isolated from hospital wastewaters in Tehran. Proper antibiotics prescription and appropriate hospital wastewater treatment can prevent resistance genes in E. coli from circulating in the environment.